(untitled) (Iraqi Journal of Civil Engineering, 2022)
The influence of concrete mixing water quality on the compressive strength of concretes was investigated in this study. During the study, the compressive strength (CS) of the concretes was determined at 7, 14, and 28 days age. This study used 8 types of water of varying qualities as concrete mixing water (water with 71 UTN impurity level, water with 250 UTN impurity level, water with 1000 UTN impurity level, well-sourced water, acidified water, and alkaline water). Potable water was used as reference water. The results indicated that the lowest CS has been obtained by using alkaline water at a concrete age of 7 days while the usage of water with 250 UTN impurity level as a concrete mixing water yielded the highest CS. in addition, the lowest CS has been obtained when using a mixing water of alkaline at a concrete age of 14 days while the highest CS resulted from using water with 71 and 250 UTN impurities levels. Furthermore, the usage of water with 71 UTN impurities level and an acidic water as a concrete water mixing gave the lowest CS at twenty eight days concrete age, while using magnetic water and water with 250 UTN impurities as concrete mixing water resulted in the highest CS. The use of water with 250 UTN impurities as concrete mixing water favored CS development at all concrete ages. These obtained results have shown a various effects of different impurities which significantly indicate that only a few water impurities affect the concrete’s CS seriously..